Brain atrophy in middle‐aged subjects with Type 2 diabetes mellitus, with and without microvascular complications: 合并或者不合并微血管并发症的中年2型糖尿病受试者的脑萎缩研究. Issue 8 (11th March 2018) - Fang, Fang; Zhan, Ya‐Feng; Zhuo, Yao‐Yao; Yin, Da‐Zhi; Li, Kang‐An; Wang, Yu‐Fan
Abstract: Background: The rapid rise in Type 2 diabetes mellitus (T2DM) among young adults makes it important to understand structural changes in the brain at a presenile stage. This study examined global and regional brain atrophy in middle‐aged adults with T2DM, with a focus on those without clinical evidence of microvascular complications. Methods: The study recruited 66 dementia‐free middle‐aged subjects (40 with T2DM, 26 healthy volunteers [HVs]). Patients were grouped according to the presence (T2DM‐C; n = 20) or absence (T2DM‐NC; n = 20) of diabetic microvascular complications. Global brain volume (including gray matter [GM] and white matter) was calculated based on voxel‐based morphometry analysis. Regional GM volumes were further extracted using the anatomical automatic labeling template. Results: There was a significant difference in global brain volume among groups ( P = 0.003, anova ). Global brain volume was lower in T2DM‐C patients than in both T2DM‐NC patients and HVs (mean [±SD] 0.720 ± 0.024 vs 0.736 ± 0.021 and 0.743 ± 0.019, respectively; P = 0.032 and P = 0.001, respectively). Regional analysis showed significant GM atrophy in the right Rolandic operculum ( t = 3.42, P = 0.001) and right superior temporal gyrus ( t = 2.803, P = 0.007) in T2DM‐NC patients compared with age‐ and sex‐matched HVs. Conclusions: Brain atrophy is present in dementia‐free middle‐aged adults with T2DM. Regional brain atrophy appears to be developing even in those with no clinical evidence of microvascular disturbances. The brain seems to be particularly vulnerable to metabolic disorders prior to peripheral microvascular pathologies associated with other target organs. Abstract : Highlights Brain atrophy is present in dementia‐free middle‐aged adults with Type 2 diabetes mellitus (T2DM). Regional brain atrophy appears to be developing even in subgroup that shows no clinical evidence of microvascular disturbances. The brain seems to be particularly vulnerable to metabolic disorders prior to peripheral microvascular pathologies associated with other target organs.